The Effect of Cyberspace-Based Education on Caregivers Burden in Caregivers Who Care about Elderly with Dementia - Mollaei 1, Parisa; Taheri Tanjani 2, Parisa; Abolfathi Momtaz 3, Yadollah; Ghaffari 4*, Mohtasham (Shahroud Journal of Medical Sciences, 2019)
Background: Dementia prevalence is identified as one of the consequences of aging. Care for patients with dementia has significant consequences for caregivers like poorer physical health, emotional stresses, depression and high mortality risk. This study was accomplished in order to determine the cyber-based education effect on care burden in caregivers of elderly with dementia. Methods: : This study is a quasi- experimental study performed on 86 caregivers of elderly with dementia who were referred to the Taleghani Hospital. This study samples were selected in both intervention and control groups as available sampling. Data collection tool was Zarit's care burden Questionnaire that was completed by using telephone interview (before and by passing two months from the end of intervention). Cyberspace-based educational intervention was conducted for one month, in the form of videos, clips, photo and text. The collected data were analyzed using SPSS software version 16 by applying Chi-square, independent t-test and paired t-test. Results:This study population included 86 participants (43 people in the intervention group and 43 people in the control group). The questionnaire reliability in this study was 0.92 (Cronbach's alpha=0.92) and the physical and psychology dimensional reliability were measured as 0.75 and 0.9, respectively. Results indicated significant changes in the reduction of total care burden after education in the intervention group (P.V <0.001). Moreover, the amount of physical burden (P < 0.001) and psychological burden (P < 0.001) have reduced after intervention.Conclusions:Conclusions: With respect to finding, cyber- based learning is suggested for caregivers of elderly with dementia in order to reduce the care burden. Keywords: Care burden, Caregivers, Dementia, Elderly, Education based on cyber.